2017
DOI: 10.1080/17470218.2015.1099162
|View full text |Cite
|
Sign up to set email alerts
|

The SPOT Effect: People Spontaneously Prefer their Own Theories

Abstract: People often exhibit confirmation bias: they process information bearing on the truth of their theories in a way that facilitates their continuing to regard those theories as true. Here, we tested whether confirmation bias would emerge even under the most minimal of conditions. Specifically, we tested whether drawing a nominal link between the self and a theory would suffice to bias people towards regarding that theory as true. If, all else equal, people regard the self as good (i.e., engage in self-enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 77 publications
(84 reference statements)
0
24
0
3
Order By: Relevance
“…For example, even prisoners consider themselves more prosocial than nonprisoners (Sedikides, Meek, Alicke, & Taylor, 2014). In addition, the effect is larger among people with higher socio-economic status (Varnum, 2015), and made-up theories attributed to oneself are preferred more than theories attributed to strangers or no-one (Gregg, Mahadevan, & Sedikides, 2017). Source.…”
Section: Perceptions Of Other Peoplementioning
confidence: 99%
“…For example, even prisoners consider themselves more prosocial than nonprisoners (Sedikides, Meek, Alicke, & Taylor, 2014). In addition, the effect is larger among people with higher socio-economic status (Varnum, 2015), and made-up theories attributed to oneself are preferred more than theories attributed to strangers or no-one (Gregg, Mahadevan, & Sedikides, 2017). Source.…”
Section: Perceptions Of Other Peoplementioning
confidence: 99%
“…Additionally, according to research inspired by self-perception and self-signaling theories, choice serves as a signal manifesting not only to others but also to the self what one likes and what kind of a person one is (Bem, 1967;Bodner & Prelec, 2003;Quattrone & Tversky, 1984). Finally, research on associative self-anchoring has shown that, when individuals make choices, implicit self-evaluations are transferred from the self to the chosen options, so that choosers end up liking what they select, because they see themselves reflected in their choices (Gawronski, Bodenhausen, & Becker, 2007;Ye & Gawronski, 2016; see also Gregg, Mahadevan, & Sedikides, 2017).…”
Section: Consumer Choices Self-referencing and State Narcissismmentioning
confidence: 99%
“…It can be deeply counterproductive to use unpleasant euphemistic terms like 'low information' to describe actors whose views we do not respect. This is a particular problem for scholars if they assume that most people do not live up to their own imagined standards of high-information-led action while actually using similar shortcuts to reinforce and bolster their own beliefs (Gregg et al, 2016).…”
mentioning
confidence: 99%